Association between adolescent girls anxiety and parental style of control - R Karimi; T Taghavi Larijani; A Mehran; F Ghaljaei (Tehran University of Medical Sciences, 2006)
Background & Aim: In order to present any level of education and care of children by nurses, there is need to be a strong and favorite interrelationship between parents and their children. Background of this relationship must be recognized in texture of family (parental control) and regard to the duty of nurses continuance of family relationship is necessary. At the same time it must be adopted policies to compatible with child mentality and help to reduce his/her anxiety. Methods & Materials: This study is a descriptive correlation research to determine association between patterns of parental style of control with adolescents anxiety, it performed in Ten schools in Tehran in this research data have been collected with two questionnaire for (student, parents) the samples was consisted 370 students (13 to 15 years) and their parents, these instrument consisted demographic characteristics (for student and parents), Physiological indicator anxiety (for parent), and Reynolds and Richmond anxiety test for students. The data were the Analyzed by (SPSS) computer software. Results: Result show that Anxiety in the student was 33% and Anxiety 7.6% and student have been Authoritarian parents had high score of Anxiety 92%. This finding shows a significant correlation between Anxiety and parental style of control (p<0.05). Conclusion: According to the finding parent style control has important role in mental health of children. School nurses can important role in education of best style control of parenting with adolescents and decries of Anxiety from it.